2001
DOI: 10.1007/s11769-001-0030-4
|View full text |Cite
|
Sign up to set email alerts
|

A historical examination on land desertification in North China

Abstract: Desertification control has been facing severe situations in the interlocking area between cultivated land and grazing land in North China since the Qing Dynasty because of unreasonable land utilization. The paper analyzes the policies of all the previous governments to open up land, and examines the historical and geographical background and process by means of historical records. We consider that causes of the area of land desertification to extend are increase of farming migrants, the change of life style o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The interview data and meta-analysis of the literature also indicated that communication among different levels of government and between government and other social actors should also be encouraged to build a harmonious institutional change system. Thus, citizens must improve their understanding of governmental polices, but it is also essential for the government to improve its understanding of citizens' preferences, demands, ideas and hopes (Yan et al, 2001;Yang, 2009Yang, , 2010 and for individuals such as scholars and experts to improve their understanding of each other, given their heterogeneous types of knowledge (Azadi et al, 2007).…”
Section: Rule 6: Institutional Change Is a Gradual Process Punctuatedmentioning
confidence: 99%
“…The interview data and meta-analysis of the literature also indicated that communication among different levels of government and between government and other social actors should also be encouraged to build a harmonious institutional change system. Thus, citizens must improve their understanding of governmental polices, but it is also essential for the government to improve its understanding of citizens' preferences, demands, ideas and hopes (Yan et al, 2001;Yang, 2009Yang, , 2010 and for individuals such as scholars and experts to improve their understanding of each other, given their heterogeneous types of knowledge (Azadi et al, 2007).…”
Section: Rule 6: Institutional Change Is a Gradual Process Punctuatedmentioning
confidence: 99%